2012
DOI: 10.1038/nn.3080
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary recent neuroepithelial cell adhesion function of huntingtin implicates ADAM10-Ncadherin

Abstract: The Huntington's disease gene product, huntingtin, is indispensable for neural tube formation, but its role is obscure. We studied neurulation in htt-null embryonic stem cells and htt-morpholino zebrafish embryos and found a previously unknown, evolutionarily recent function for this ancient protein. We found that htt was essential for homotypic interactions between neuroepithelial cells; it permitted neurulation and rosette formation by regulating metalloprotease ADAM10 activity and Ncadherin cleavage. This f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 50 publications
10
82
1
2
Order By: Relevance
“…For inhibition of ADAM-10 dependent Hla-mediated lysis, peritoneal cells were pre-incubated with 80μM GI254023X (Okeanos Tech.) for 60min at 37°C followed by addition of a two-fold stock Hla leading to a final concentration of 40μM GI254023X 49 and 10μg/ml of Hla in the cell suspension which was incubated for a further 20–30 minutes. Following incubation, cells were washed in FACS buffer and stained with anti-CD19 APC-Cy7 or PE (clone 1D3), anti-CD11c PE-Cy7 (clone HL3), anti-CD11b FITC (clone M1/70) and anti-F4/80 PE (clone BM8) or A647 (clone: CI:A3-1) antibodies (all purchased from BD or AbD Serotec) and assessed by flow cytometry using 10-laser LSR II cytometer (BD).…”
Section: Methodsmentioning
confidence: 99%
“…For inhibition of ADAM-10 dependent Hla-mediated lysis, peritoneal cells were pre-incubated with 80μM GI254023X (Okeanos Tech.) for 60min at 37°C followed by addition of a two-fold stock Hla leading to a final concentration of 40μM GI254023X 49 and 10μg/ml of Hla in the cell suspension which was incubated for a further 20–30 minutes. Following incubation, cells were washed in FACS buffer and stained with anti-CD19 APC-Cy7 or PE (clone 1D3), anti-CD11c PE-Cy7 (clone HL3), anti-CD11b FITC (clone M1/70) and anti-F4/80 PE (clone BM8) or A647 (clone: CI:A3-1) antibodies (all purchased from BD or AbD Serotec) and assessed by flow cytometry using 10-laser LSR II cytometer (BD).…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be considered that long-term regulation of at least ADAM10 and ADAM17 will be challenging, given the pronounced phenotypes of ADAM10 and 17 knockout mouse models. Development 139 (20) by the regulation of ADAM10 and N-cadherin (cadherin 2) shedding (Lo Sardo et al, 2012). …”
mentioning
confidence: 99%
“…1C), indicating that the survival of oocytes was not affected by inhibiting ADAM10. In addition, we cultured ovaries with another ADAM10 selective inhibitor GI254023X (Hoettecke et al, 2010;Hundhausen et al, 2003;Lo Sardo et al, 2012). The results showed that 7 days of GI254023X treatment also significantly decreased the number of follicles (1138.0±184.0 per ovary for GI254023X versus 8188.0±1152.3 per ovary for control; Fig.…”
Section: Suppressing Adam10 Disrupts Germline Cyst Breakdown and Primmentioning
confidence: 88%